CYP3A5 influences oral tacrolimus pharmacokinetics and timing of acute kidney injury following allogeneic hematopoietic stem cell transplantation - Seligson, Nathan D.; Zhang, Xunjie; Zemanek, Mark C.; Johnson, Jasmine A.; VanGundy, Zachary; Wang, Danxin; Phelps, Mitch A.; Roddy, Julianna; Hofmeister, Craig C.; Li, Junan; Poi, Ming J. (Frontiers in Pharmacology, 2024)
Introduction: Polymorphisms in genes responsible for the metabolism and transport of tacrolimus have been demonstrated to influence clinical outcomes for patients following allogeneic hematologic stem cell transplant (allo-HSCT). However, the clinical impact of germline polymorphisms specifically for oral formulations of tacrolimus is not fully described. Methods: To investigate the clinical impact of genetic polymorphisms in CYP3A4, CYP3A5, and ABCB1 on oral tacrolimus pharmacokinetics and clinical outcomes, we prospectively enrolled 103 adult patients receiving oral tacrolimus for the prevention of graft-versus-host disease (GVHD) following allo-HSCT. Patients were followed in the inpatient and outpatient phase of care for the first 100 days of tacrolimus therapy. Patients were genotyped for CYP3A5 *3 (rs776746), CYP3A4 *1B (rs2740574), ABCB1 exon 12 (rs1128503), ABCB1 exon 21 (rs2032582), ABCB1 exon 26 (rs1045642). Results: Expression of CYP3A5 *1 was highly correlated with tacrolimus pharmacokinetics in the inpatient phase of care (p<0.001) and throughout the entirety of the study period (p<0.001). Additionally, Expression of CYP3A5 *1 was associated with decreased risk of developing AKI as an inpatient (p=0.06). Variants in ABCB1 were not associated with tacrolimus pharmacokinetics in this study. We were unable to discern an independent effect of CYP3A4 *1B or *22 in this population. Conclusion: Expression of CYP3A5 *1 is highly influential on the pharmacokinetics and clinical outcomes for patients receiving oral tacrolimus as GVHD prophylaxis following allo-HSCT.